Partisipasi dan Kontribusi Perempuan dalam Mendukung Program Nawacita di Kelurahan Bendogerit Kota Blitar Tahun 2015 - Indra Kurniawati (Indonesian Journal of Women's Studies, 2016)
Women's participation is an important aspect of economic development. Participation is one of the three elements of development-oriented community in addition to justice and empowerment element. Women's participation is a decisive factor and also as an indicator of successful development. Women have a strong bond with the environment. This study aimed to describe women's participation in the waste sanitation program to support the program in the Bendogerit Village to support Nawacita Program in Blitar City 2015. This study used a qualitative method with descriptive models. The Subjects in this study were mothers as the members of Women Farmers Group "Putri Rahayu" who active in the Garbage Bank program "Anggrek" in the Bendogerit Village. The data used in the research is the source of primary data and secondary data sources. Data collection technique used In-depth Interviews, observation, literature study, and documentation. Women's participation in sanitation programs in Bendogerit village can be shown in the Garbage Bank ”Anggrek”. Women's Participation in waste sanitation program to support Nawacita programs in Bendogerit Village Blitar City, can be shown with some of the activities of women's participation in the processing of the waste. Women's participation in the planning stages on household waste management seen from their participation in activity planning meeting. Forms of participation of women in the management of household waste in Bendogerit village can be seen from the participation of the members of Garbage Bank “Anggrek” channeling with their creativity to transform plastic waste that can not be used as goods which have high sales value. The stage of enjoying the views of the economic results they get from following the activities of the management of household waste. The Constraints implementation of sanitation programs in Bendogerit village waste is located on capital funding. The Garbage Bank “Anggrek”  have not registered their main products on the part of taxpayers, so that the government of Blitar difficult to deliver assistance in the form of money for capital development  of the Garbage Bank “Anggrek”. The women's participation in the implementation of the Garbage Bank “Anggrek” is very important role in independent economic for improvingthat oriented in Tourism Industry and Creative Economy which competitive and environmentally weather.